How should China prioritize the deregulation of electricity prices in the context of carbon pricing? A computable general equilibrium analysis - Zhang, Kun; Yao, Yun-Fei; Liang, Qiao-Mei; Saren, Gaowa (Energy economics, 2021)
China formally launched a national carbon trading market in the power sector in 2017. However, electricity prices in China are still subject to government regulation, which reduces the cost-effectiveness of the carbon pricing policy. This study uses a computable general equilibrium model to explore how China's electricity prices can be deregulated in two stages in the context of implementing carbon pricing in the electricity sector. The results show that under different government policy objectives, the choice of electricity price deregulation is different. If the government intends to significantly reduce marginal abatement costs and promote carbon emission reductions, the electricity price deregulation of non-key electricity consumption sectors should be prioritized in the first stage and that of the national protected sectors in the second stage. Conversely, if the government intends to reduce GDP losses, households' disposable income, and welfare losses effectively, the liberalization of the electricity prices of key electricity consumption sectors should be prioritized in the first stage and that of the household sector in the second stage. Taking 50% of the reduction targets in the electricity sector as an example, if the key electricity consumption sectors and households are prioritized, GDP losses are reduced by 3.6% and 13%, respectively. The results of this study provide new information for China to implement electricity market reform in the context of carbon pricing. •Explore the electricity prices deregulation in the context of carbon pricing.•Priority of electricity price release is different under various policy objectives.•The deregulation of electricity prices could reduce the marginal abatement cost.•Deregulation is conducive to protect the economy under a high mitigation target.